Assessment of avian erythrocytes that exhibit variant nuclear morphology - Clark, Phillip (2015)
Avian erythrocytes are predominately nucleated with a typically ovoid, central nucleus composed of dense chromatin. However, some erythrocytes exhibit a variant nuclear morphology. The current study assessed blood films from 70 birds that encompassed 50 species and 16 orders, to determine the presence of erythrocytes with variant nuclear morphology. Overall, erythrocytes with variant nuclear morphology were recognised in the blood from 35/70 (50 %) birds. The most commonly encountered morphological variant was erythrocytes with a symmetrical constricted nucleus, with lesser numbers of the other variants; indented, bi-lobed/bi-nucleated, asymmetrical constricted and micro-lobed/micro-nucleated cells recognised. In the birds that had erythrocytes with variant nuclear morphology present, the mean concentration was 10.87 × 109/l. The current study demonstrates that a small proportion of erythrocytes with variant nuclear morphology can be detected in a wide range of birds. © 2014 Springer-Verlag London.